2021
DOI: 10.1017/cjn.2021.208
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Mannosidosis: A Novel Cause of Bilateral Thalami and Dentate Nuclei Hyperintensity

Abstract: Alpha-mannosidosis is a rare autosomal recessive lysosomal storage disorder caused by mutations in the MAN2B1 gene. 1 To date, a total of 154 variants have been identified in 191 patients worldwide. 1 Symptoms usually begin in childhood, but milder forms may present only in adulthood. The most frequent systemic findings include skeletal abnormalities (81%), facial dysmorphia (70%), deafness (67%), immunodeficiency (recurrent respiratory tract infections; 53%), and organomegaly (namely, hepatosplenomegaly; 41%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Upon the analysis of MRI brain images of 13 patients with AM, Majovska et al concluded that white matter changes and cerebellar atrophy are proposed to be the characteristic brain MRI features in this condition [Figure 2] [30] .…”
Section: Neuroimagingmentioning
confidence: 99%
“…Upon the analysis of MRI brain images of 13 patients with AM, Majovska et al concluded that white matter changes and cerebellar atrophy are proposed to be the characteristic brain MRI features in this condition [Figure 2] [30] .…”
Section: Neuroimagingmentioning
confidence: 99%